Impact of programming in a large cohort of implantable cardioverter-defibrillator patients with long-term follow-up: findings from the UMBRELLA study. (14th October 2021) - Briongos Figuero, S; Garcia Alberola, A; Rubio, J B; Segura, J M; Rodriguez, A; Peinado, R; Alzueta, J; Martinez Ferrer, J B; Vinolas, X; Munoz-Aguilera, R; Perez, M L
Abstract: Background: Data about the penetration of current ICD programming recommendations in a real-life setting are lacking. Purpose: To assess how modern-era ICD patients are programmed and to study the relationship between programming and ICD therapies in large cohort of Spanish patients. Methods: UMBRELLA (NTC01561144) is a prospective, multicentre, nationwide study of ICD patients followed by remote monitoring. ICD programming was performed according to regular clinical practice at each site and it was automatically stored through the remote monitoring system. Arrhythmic events were also automatically stored and reviewed in a blinded process performed by a committee of experts. The study outcomes were appropriate ICD therapies and inappropriate shocks (IS). Results: The study population consisted of 4296 patients implanted with an ICD from 2005 to 2017 (61.9±12.9 years, ischaemic cardiomyopathy in 50% and dilated cardiomyopathy in 22.7% of population). Primary prevention (PP) was the main indication (64.2%). At implant, 66.4% of patients had LVEF ≤35% and 18.9% had LVEF >50%. Majority of patients (52.4%) presented with narrow QRS (<120 ms), while QRS width was >150 ms in 26.7% of population. Single-chamber, dual-chamber and cardiac resynchronization therapy-defibrillator (CRT-D) devices were implanted in 47.2%, 22.6% and 30.2% of population, respectively. At first remote transmission, single zone detection programming was only enabled in 43.2% of population (52.6% among PP patients), while the remaining patients (56.8%) had a ventricular tachycardia zone enabled, despite the ventricular fibrillation (VF) zone (73.8% among secondary prevention patients). Delayed high-rate detection programming (detection interval <320 ms and NID ≥30/40 within the VF zone) was only enabled in 39.7% of population. Adherence to programming recommendations significantly increased through the study period (Table). During a mean follow-up of 46.6±27.3 months, 16, 067 episodes of sustained ventricular arrhythmia (SVA) occurred. An appropriate ICD therapy was delivered to 85.7% (n=13, 767) episodes of SVA in 1173 patients (event rate: 27.3%). In multivariate analysis, delayed high-rate detection in PP patients (HR: 0.76, 95% CI: 0.61–0.94) (Figure) and single-zone programming (HR: 0.69, 95% CI: 0.59–0.81) were associated to lower risk of appropriate ICD therapies. At follow-up, 257 patients (6% of population) experienced an IS. The incidence of IS did not differ according to type of device (6.4% vs. 6.2% vs. 5.2% for single-, dual-chamber, and CRT-D, respectively, p=0.321). In multivariate analysis single-zone programming (HR: 0.71, 95% CI: 0.51–0.97) was the only ICD setting independently related to a lower risk of IS. Conclusions: Implementation of current programming recommendations is required in modern-era ICD patients. Funding Acknowledgement: Type of funding sources: None.